2010
DOI: 10.1186/1744-8069-6-94
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Rat TRPV1-Expressing Adelta/C-Fibers with Resiniferatoxin: Analysis of Withdrawal Behaviors, Recovery of Function and Molecular Correlates

Abstract: BackgroundAblation of TRPV1-expressing nociceptive fibers with the potent capsaicin analog resiniferatoxin (RTX) results in long lasting pain relief. RTX is particularly adaptable to focal application, and the induced chemical axonopathy leads to analgesia with a duration that is influenced by dose, route of administration, and the rate of fiber regeneration. TRPV1 is expressed in a subpopulation of unmyelinated C- and lightly myelinated Adelta fibers that detect changes in skin temperature at low and high rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
89
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 58 publications
15
89
0
Order By: Relevance
“…Cutaneous afferents were activated either by low-rate (Յ1.5°C) heating using long pulses, low energy, and a large diameter beam (5 mm Ø, nominal) or by a high rate (Ն150°C) of heating, using a high-energy, short pulse (100 ms), and a small beam diameter (1.6 mm Ø, nominal). Under these parameters, long pulses preferentially activate C-fibers, and short pulses preferentially activate A␦ fibers (32,33). Longpulse responses were evaluated at three laser current settings, 650, 750, and 850 mA, and short-pulse responses were evaluated at 2500, 3000, 3500, and 4000 mA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous afferents were activated either by low-rate (Յ1.5°C) heating using long pulses, low energy, and a large diameter beam (5 mm Ø, nominal) or by a high rate (Ն150°C) of heating, using a high-energy, short pulse (100 ms), and a small beam diameter (1.6 mm Ø, nominal). Under these parameters, long pulses preferentially activate C-fibers, and short pulses preferentially activate A␦ fibers (32,33). Longpulse responses were evaluated at three laser current settings, 650, 750, and 850 mA, and short-pulse responses were evaluated at 2500, 3000, 3500, and 4000 mA.…”
Section: Methodsmentioning
confidence: 99%
“…We could not detect any change in both p35 and Cdk5 protein levels in DRG and TG, as well as in Cdk5 activity in TG and DRG from postnatal 45-day-old Tgfbr1 cKO compare with control mice (data not shown). To evaluate whether pain sensation was affected in Tgfbr1 cKO mice, acute nociceptive responses were measured using an infrared diode laser to activate cutaneous thermal nociceptive nerve endings (33) in the hind paws of Tgfbr1 cKO mice between 1 and 2 months of age, who showed no signs of inflammation or body FIGURE 3. TGF-␤1 increased TRPV1 phosphorylation resulting in increased intracellular Ca 2؉ influx in DRG primary culture.…”
Section: Decreased Cdk5 Activity and Attenuated Responses To Thermal mentioning
confidence: 99%
“…Administration of a vanilloid agonist, such as capsaicin or its ultrapotent analog RTX [31], can cause calcium-induced cytotoxicity and lead to a TRPV1-selective axonopathy that spares surrounding non-TRPV1-expressing somatosensory proprioceptive afferent and motor efferent nerve fibers. The potency and selectivity of vanilloid agonists for TRPV1 afferents has been demonstrated repeatedly in vivo [8,[32][33][34][35][36][37][38][39][40]. For example, ablation of TRPV1 + nerve terminals occurring after a single subcutaneous injection of RTX into the rat hind paw results in prolonged but reversible analgesia that can be detected for one to several weeks and induces up-regulation of molecular markers for axon damage/repair in neuronal perikarya of the dorsal root ganglia [8,32].…”
Section: Introductionmentioning
confidence: 99%
“…The potency and selectivity of vanilloid agonists for TRPV1 afferents has been demonstrated repeatedly in vivo [8,[32][33][34][35][36][37][38][39][40]. For example, ablation of TRPV1 + nerve terminals occurring after a single subcutaneous injection of RTX into the rat hind paw results in prolonged but reversible analgesia that can be detected for one to several weeks and induces up-regulation of molecular markers for axon damage/repair in neuronal perikarya of the dorsal root ganglia [8,32]. We have also found that topical application of RTX onto the cornea results in temporary loss of the capsaicin eyewipe response in parallel with a loss of CGRP immunoreactive afferents in stromal fiber bundles [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation